Gerai Nor / Harith Danial A.S. Azmi … [et al.] - A.S. Azmi, Harith Danial; Anuar, Muhamad Hakim; Roslan, Muhammad Hazim; Omar, Muhammad Zahiruddin (2022)
Since 2000, Gerai Nor has been a local favorite since it is located at a strategic location. Gerai Nor is a small stall and local eatery located at G-9, Pusat Bandar, Bandar Al Muktafi Billah Shah, 23400 Dungun, Terengganu. Gerai Nor set a price below RM3 for their foods and beverages which makes it extremely affordable for the customers. Gerai Nor sells about 9 different types of foods and beverages, including 4 different foods and 5 different beverages. Gerai Nor employs 3 people, 2 of them are in charge of business operations and marketing while the other one is a delivery rider. The owner of Gerai Nor, Puan Nor Roshamiza Binti Abu Bakar, first opened this small stall on December 20, 2000, and it has been almost 22 years since then. Despite the fact that Gerai Nor is currently implementing an excellent operational plan, we have discovered that the stall still requires and recommends a number of problems and improvements. In conclusion, this report summarizes the findings of a case study conducted on Gerai Nor as a whole, including the company's background, operations, products and services offered, problems and challenges, and recommendations.